How Tourism Imaginary has been Updated in the New Spanish Sun-and-Beach Comedy: Fin de curso, Atasco en la nacional and Benidorm, mon amour - Salvador Martínez Puche; Antonio Martínez Puche (Via@)
In the late-Francoist period, coastal tourism became an extremely important argument and discourse in film fiction and coincided with what was known as comedia desarrollista. This ‘development-era’ comedic film production was prolific, successful and in line with Spain’s propaganda, political and socioeconomic interests in the 1960s and 1970s. Its narrative and expressive codes can still be found in films that fall into the españolada supra-genre and use some of those clichés—now recycled and updated—in their form and content. An analysis of three feature films, Fin de curso (School’s Out, 2005), Atasco en la nacional (Traffic Jam, 2007)and Benidorm, mon amour (2015), shows how the stereotypical representation of sun-and-beach tourism, rather superfluous in the twenty-first century, has been influenced by deeply rooted imaginaries that previously served to promote the country’s commodified offerings.